Time-domain full-field optical coherence tomography (TD-FF-OCT) in ophthalmic imaging - Jinze Zhang; Viacheslav Mazlin; Keyi Fei; Albert Claude Boccara; Jin Yuan; Peng Xiao (SAGE Publishing, 2023)
Ocular imaging plays an irreplaceable role in the evaluation of eye diseases. Developing cellular-resolution ophthalmic imaging technique for more accurate and effective diagnosis and pathogenesis analysis of ocular diseases is a hot topic in the cross-cutting areas of ophthalmology and imaging. Currently, ocular imaging with traditional optical coherence tomography (OCT) is limited in lateral resolution and thus can hardly resolve cellular structures. Conventional OCT technology obtains ultra-high resolution at the expense of a certain imaging range and cannot achieve full field of view imaging. In the early years, Time-domain full-field OCT (TD-FF-OCT) has been mainly used for ex vivo ophthalmic tissue studies, limited by the low speed and low full-well capacity of existing two-dimensional (2D) cameras. The recent improvements in system design opened new imaging possibilities for in vivo applications thanks to its distinctive optical properties of TD-FF-OCT such as a spatial resolution almost insensitive to aberrations, and the possibility to control the curvature of the optical slice. This review also attempts to look at the future directions of TD-FF-OCT evolution, for example, the potential transfer of the functional-imaging dynamic TD-FF-OCT from the ex vivo into in vivo use and its expected benefit in basic and clinical ophthalmic research. Through non-invasive, wide-field, and cellular-resolution imaging, TD-FF-OCT has great potential to be the next-generation imaging modality to improve our understanding of human eye physiology and pathology.